2006
DOI: 10.1002/eqe.593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of residual drift demands in regular multi-storey frames for performance-based seismic assessment

Abstract: This paper summarizes results of a comprehensive analytical study aimed at evaluating the amplitude and heightwise distribution of residual drift demands in multi-storey moment-resisting frames after earthquake excitation. For that purpose, a family of 12 one-bay two-dimensional generic frame models was subjected to an ensemble of 40 ground motions scaled to different intensities. In this investigation, an inelastic ground motion intensity measure was employed to scale each record, which allowed reducing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 8 publications
4
49
1
Order By: Relevance
“…Regarding system level studies, it has been deemed that several factors directly associated with the variability of ground motion parameters and the inherent characteristics of MDOF systems have profound implication for amplitude and allocation of RD demands [9]. Besides, it is noteworthy that the type of hysteretic models in systems exhibiting stiffnessdegrading behavior considerably influences the level of residual deformation demands [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding system level studies, it has been deemed that several factors directly associated with the variability of ground motion parameters and the inherent characteristics of MDOF systems have profound implication for amplitude and allocation of RD demands [9]. Besides, it is noteworthy that the type of hysteretic models in systems exhibiting stiffnessdegrading behavior considerably influences the level of residual deformation demands [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the distributions of peak story drifts, peak residual story drifts and peak total floor accelerations along the building height depend on the fundamental period of vibration, number of stories and level of inelastic deformation [32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have recognized that the residual drift is a useful and advanced design criterion in performance-based design [38,39]. Nowadays, in both new seismic design and seismic assessment of the existing building, special attention is paid by researchers for mitigating damage of non-structural component and preventing residual displacement after earthquake (i.e.…”
Section: Residual Drift Responsesmentioning
confidence: 99%